2018
DOI: 10.3892/mmr.2018.8427
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of IL-23/IL-23R in patients with breast cancer and its clinical significance

Abstract: Breast cancer tissues and adjacent tissues were collected from 32 patients who were treated in The Third Hospital of Chengde City. Reverse transcription‑quantitative polymerase chain reaction results demonstrated that, compared with the adjacent tissues, interleukin (IL)‑23/IL‑23 receptor (R) gene expression levels were notably higher in breast cancer tissues. Furthermore, IL‑23 and IL‑23R expression levels were positively correlated with patients' tumor size, TNM stage and metastasis. Recombinant human (rh) I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Another proinflammatory cytokine, IL‐23, also plays important roles in inducing Th17 cell proliferation and tumor development in breast cancer . In addition to inducing IL‐17 expression, IL‐23 inhibits apoptosis of MCF‐7 breast cancer cells, thus promoting tumor progression .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another proinflammatory cytokine, IL‐23, also plays important roles in inducing Th17 cell proliferation and tumor development in breast cancer . In addition to inducing IL‐17 expression, IL‐23 inhibits apoptosis of MCF‐7 breast cancer cells, thus promoting tumor progression .…”
Section: Discussionmentioning
confidence: 99%
“…Another proinflammatory cytokine, IL‐23, also plays important roles in inducing Th17 cell proliferation and tumor development in breast cancer . In addition to inducing IL‐17 expression, IL‐23 inhibits apoptosis of MCF‐7 breast cancer cells, thus promoting tumor progression . Moreover, levels of IL‐23 and IL‐23R expression are positively correlated with tumor size, tumor‐node‐metastasis stage and metastasis in breast cancer, suggesting a significant role for IL‐23 in the pathogenesis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as we have previously reported, Paget's cells as well as dermal myeloid cells produce IL-23, leading to the induction of IL-17 in the lesional skin in extramammary Paget's cells [7]. In addition to inducing IL-17 expression, IL-23 inhibits apoptosis; thus, promoting tumor progression [6]. In aggregate, IL-23 could be a key trigger for the induction of IL-17, leading to IL-17-producing cells in skin cancers.…”
Section: Discussionmentioning
confidence: 79%
“…IL-23 plays an important role in inducing Th17 cell proliferation as well as in the angiogenesis of tumors [3][4][5][6][7]. Indeed, Nie et al [4] reported that IL-23 promotes the recruitment of M2 macrophages and neutrophils, which secrete immunosuppressive cytokines and vascular endothelial growth factor as well as matrix metalloproteinase 9 (MMP9) into tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokines IL-23 and IL-17 could play crucial roles in tumor development in cutaneous SCC. 4,5 In addition to inducing IL-17, IL-23 inhibits tumor cell apoptosis, clinically affecting the tumor progression. IL-17 induces the proliferation of keratinocytes and tumorigenesis, including that of cutaneous SCC.…”
mentioning
confidence: 99%